Modernization of land registry by adapting blockchain with Proof-of-Work (PoW) - Mostofa, Sabrina Israt; Mahmud, Tasin; Adrito, Bivor Faruque; Roy, Tridiv (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.